1999
DOI: 10.1007/bf02475766
|View full text |Cite
|
Sign up to set email alerts
|

Reactions ofn-hexane andn-nonane on Pt catalysts and hydrogenating off hydrocarbonaceous adspecies after reaction

Abstract: Abstractn-Hexane and n-nonane were reacted on Pt black, 6% Pt/SiO2, 0.8% Pt/KL zeolite and a 0.6% industrial Pt/A1203 catalyst. Selectivities were compared at -10% conversion. After reaction, the catalyst was exposed to 1-I2 and the hydrocarbons leaving the catalysts were analyzed. The amount of hydrocarbons left the catalysts decreased in the sequence Pt black> Pt/SiO2> Pt/KL>Pt/A1203. The composition of removed hydrocarbons gave important -although indirectinformation on the possible state of "hydrocarbonace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This latter process may be important in regeneration and can lead to carbon removal as methane. 49 Skeletal reactions of n-hexane reportedly require various active sites. They are ensembles of threefold symmetry for benzene formation,50 two neighbouring atoms for ring C 5 closure and opening51 while larger ensembles may possibly be active for fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…This latter process may be important in regeneration and can lead to carbon removal as methane. 49 Skeletal reactions of n-hexane reportedly require various active sites. They are ensembles of threefold symmetry for benzene formation,50 two neighbouring atoms for ring C 5 closure and opening51 while larger ensembles may possibly be active for fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pt adsorbs the hydrocarbons; therefore, a chemical reaction not only has taken place with adamantane but also may have taken place with hexane (C 6 H 14 ). Previous studies have shown that the hexane can react with Pt . The melting point of Pt (∼1772 °C) is much higher than the growth temperatures used in this study.…”
Section: Resultsmentioning
confidence: 74%
“…Previous studies have shown that the hexane can react with Pt. 47 The melting point of Pt (∼1772 °C) is much higher than the growth temperatures used in this study. The solid solubility of C in Pt is less than 1 atom % at 650 °C according to the PtÀC binary phase diagram.…”
Section: Resultsmentioning
confidence: 77%